2020
DOI: 10.4236/ojgas.2020.1011027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender Difference on Characteristics and Outcome of Chronic Hepatitis C

Abstract: Gender difference in chronic hepatitis C (CHC) infection is not previously well studied. We aimed to analyze the effect of gender difference on the risk factors of CHC, disease progression, and outcome after oral direct acting antiviral (DAA) therapy. The study was conducted at Tropical Medicine and Gastroenterology Department, Sohag University, Egypt, in the period between 2018 and 2020. 775 patients were evaluated for hepatitis C virus (HCV) risk factors. Laboratory investigations, abdominal ultrasound and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Similar findings were seen in other studies. 15,[29][30][31] In the literature, reports of sex differences in the treatment of HCV GT3 are limited. The HCV-TARGET study 32 evaluated HCV GT 3 participants receiving sofosbuvir and ribavirin with or without peginterferon and found male sex was a negative predictor of SVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were seen in other studies. 15,[29][30][31] In the literature, reports of sex differences in the treatment of HCV GT3 are limited. The HCV-TARGET study 32 evaluated HCV GT 3 participants receiving sofosbuvir and ribavirin with or without peginterferon and found male sex was a negative predictor of SVR.…”
Section: Discussionmentioning
confidence: 99%
“…Numerically or statistically significantly higher SVR rates were observed in females treated with PEG‐INF and ribavirin 13,14 compared to males and overall females reported more adverse events. With more effective combination DAA regimens, females had a slightly higher SVR12 rate compared to males (99.4% vs 97.9%) in a recent observational study 15 . More side effects were reported in females compared to males and fatigue and GI upset events were significantly higher in females 10 …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, some studies found gender differences are artifactual, with nearly flat rates of HCV infection 12 15 . Also, some studies found a decreased rate of liver cirrhosis and hepatocellular carcinoma (HCC) in females 16 , more progress to hepatic fibrosis in males, and more liability to adverse events of direct-acting antivirals (DAAs) in females 17 .…”
Section: Introductionmentioning
confidence: 99%
“…6 The scale of these enzymes is classically used to provide information about viral hepatitis infections if the main disorder is biliary hepatitis, and knowing the percentage of enzymes in the sera of infected people, as well as knowing the patterns, provides abundant information for diagnosing the pathological condition. 7,8 There are multiple blood abnormalities accompanying chronic viral hepatitis, such as iron deficiency anemia, 9 which are frequent complications of chronic liver diseases. These are caused by many factors, including chronic bleeding in the digestive system.…”
Section: Introductionmentioning
confidence: 99%